TRAINING IN DEVELOPING CHILD STORYTELLING COMMUNICATION PATTERNS IN PKK MEMBERS RPTRA DREAM PATTERN: PELATIHAN PENGEMBANGAN POLA KOMUNIKASI STORY TELLING ANAK PADA ANGGOTA PKK RPTRA POLA IDAMAN - Cindya Yunita Pratiwi; RR. Roosita Cindrakasih; Riastri Novianita; Bobby Octavia Yuskar; Vika Yustia; Debby Andra Fortuna; Reva Widyanti (Yayasan Education and Social Center, 2022)
Early childhood education is an educational program launched by the government to meet the growth and development needs of children. Early childhood education is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli to help the growth and development of children's physical and spiritual so that children have readiness to enter further education. One of the activities that can develop children's language intelligence is storytelling. Storytelling is something that is rarely done. Its role and function have been replaced by television shows and playing games on the computer. Apart from all that, stories have strengths, functions and benefits as a medium of communication, as well as a method in building a child's personality. The choice of a theme that is adapted to the linear discipline of the UBSI Campus is an absolute must, as a form of professionalism and proportion in doing community service.Seeing this, in this Community Service activity, the implementer wants to socialize the PKK RW01 RPTRA Idaman Patterns, both online using the zoom application and offline regarding the importance of storytelling in children and how to implement communication that needs to be established between parents and children through storytelling so that it is expected to develop the child's personality and intelligence